2020
DOI: 10.1016/j.jvscit.2019.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic nephrectomy with ex vivo repair of aneurysm and autotransplantation

Abstract: The perceived prevalence of renal artery aneurysms is increasing, probably because of the widespread use of crosssectional imaging. The majority of these aneurysms are found incidentally and are asymptomatic. There are no clear guidelines for when to repair these aneurysms, although most practitioners recommend intervention around the 2-to 3-cm size cutoff. These can be managed endovascularly or with open surgery; however, aneurysms at the hilum may require a complex repair to avoid nephrectomy. We present a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Among the reported cases, four patients had a solitary kidney, two patients were pregnant, and two repaired kidneys were successfully transplanted to two men, respectively, which provided benefits to both donors and recipients. 5 , 8 , 10 , 11 , 13 19 After analysis of the therapeutic strategies, we found that 47% ( N = 26) of HRAAs were treated by ex vivo reconstruction (EVR), 44% ( N = 24) were treated by in situ reconstruction (ISR), 5% ( N = 3) were treated by endovascular therapy, and 4% ( N = 2) were treated with nephrectomy. Laparoscopy was used to reduce surgical trauma owing to its lower invasiveness, and 17% ( N = 9) of the operations were performed with the aid of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Among the reported cases, four patients had a solitary kidney, two patients were pregnant, and two repaired kidneys were successfully transplanted to two men, respectively, which provided benefits to both donors and recipients. 5 , 8 , 10 , 11 , 13 19 After analysis of the therapeutic strategies, we found that 47% ( N = 26) of HRAAs were treated by ex vivo reconstruction (EVR), 44% ( N = 24) were treated by in situ reconstruction (ISR), 5% ( N = 3) were treated by endovascular therapy, and 4% ( N = 2) were treated with nephrectomy. Laparoscopy was used to reduce surgical trauma owing to its lower invasiveness, and 17% ( N = 9) of the operations were performed with the aid of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, the use of laparoscopy is limited and mostly applied for nephrectomy ( Hiess and Seitz, 2016 ; Siena et al, 2019 ; Kishore et al, 2020 ). After nephrectomy, renal vessels are extracted from the abdominal cavity and transferred to the bench table, and a separate incision is required to anastomose the renal vessels with the iliac vessels ( Kubota et al, 2020 ; Pomy et al, 2020 ; Smith et al, 2020 ). Although some studies have reported intracorporeal robot-assisted renal autotransplantation and restrictions due to kidney cold preservation in vivo , the kidney is not cold preserved continuously during the operation after vessel dissociation ( Breda et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%